Conversion of Mechanical Energy to Electrical Energy Using Piezoelectric Materials for Bicycle Lane Lighting Systems - Jettanasen, Chaiyan; Songsukthawan, Panapong; Ngaopitakkul, Atthapol (My University, 2022)
This study examined the electromechanical characteristics of piezoelectric materials, which constitute a compact renewable energy source; these materials can convert mechanical energy (such as pressure or a cumulative impact) in the form of mechanical stress to electricity. This study further explored systems that require moderate energy and utilize piezoelectric materials to create an energy-generating floor. The electrical characteristics of these piezoelectric materials were studied, including the feasibility of installing them as a power source for road lighting, particularly cycling lanes. Furthermore, the effects of riders’ weights and cycling speeds were investigated. The results indicate that the electric power generated is adequate for the installation of these materials and can thus help improve visibility in the event of insufficient lighting.
Keywords: bicycle lane; energy conversion; lighting system; piezoelectric